The great conversation : a historical introduction to philosophy (Mountain View, California. Mayfield Publishing Company., 1999)
"This third edition of The Great Conversation retains the distinctive features of the first two, representing major philosophers through extensive quotations set in a fairly rich cultural and intellectual context. It now contains, with the addition of Crito, four complete works. I continue to take the "conversation" metaphor seriously, as shown by an even larger number of cross-references, both within the text and in foot notes. I still aim to tell the dramatic story of philosophy in a lively and engaging way, hoping to draw students into the conversatio."
Includes glossary and index.
English text.
Keywords: Philosophy